The Model of Employee Experience And Productivity - Elvie Maria; Peni Cahyati; April Gunawan; Brilliant Handyman Manalu; Andriasan Sudarso (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the effect of employee experience on employee productivity in service sector companies located in West Java Province, Indonesia. Employee experience is assessed through four main dimensions: work technology, organizational culture, leadership, and employee well-being. The study adopts a quantitative explanatory research approach. Data were collected using a structured questionnaire distributed to 100 permanent employees across various service-based companies. Multiple linear regression analysis was employed using SPSS software. The results show that all dimensions of employee experience have a positive and significant effect on employee productivity, with leadership emerging as the most dominant factor. The regression model demonstrates an R square value of 0.507, indicating that 50.7% of the variability in employee productivity can be explained by the four dimensions of employee experience. These findings highlight the importance of strategically managing employee experience as an effective managerial approach to enhancing both individual and organizational performance.